Corporate strategy for a company organized to undertake the corporate farming project of a conglomerate - Magleo, Rolando Salas (Animo Repository, 1977)
The government through the National Grains Authority, had defined several methods of complying with GO 47, otherwise known as the Corporate Farming Program. For effective deliberations, management needed an in depth knowledge of the corporate farming concept and have on hand if possible, several corporate strategy proposals to serve as an initial working paper in evaluating several alternatives open to the company. The data and information were mostly gathered in the form of interviews and study of pertinent documents from the Corporate Farming Directorate of the National Grains Authority (which served as the government arm in implementing this program), the Development Bank of the Philippines (DBP), International Rice Research Institute (IRRI) and consultations with representatives of farm machinery distributors like GAMI, Aboitiz Marketing and RTC. To substantiate the project proposal, important reference materials like the Rice Production Manual published by the U.P. College of Agriculture and other important publications listed in the bibliography of this study were used. Based on the financial analysis, the corporate farming project would not only be socially beneficial but also a financially viable venture, under this proposed strategy. There would be no income in 1975 but from 1976 the return on investment would be more than 40%. Circumstances which could adversely affect the venture such as minor pest infestations, regular typhoons, etc. have already been anticipated so much so that a normal yield of only 80 cavans of palay per hectare was assumed, even if the production input budget have provided for the regular scientific recommendation, which would guarantee a yield of at least 100 cavans of palay per hectare, under regular environmental conditions. In order to break-even, a harvest of 60 cavans of palay per hectare would be needed. Revenue from the sale of the harvested crop from 1977 can cover the whole production cost making the rice farm venture self liquidating under this recommended strategy. Pa